2020
DOI: 10.1161/circinterventions.119.008649
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Intensified and Standard P2Y 12 -Receptor-Inhibition Before Elective Percutaneous Coronary Intervention

Abstract: Background: Even among biomarker-negative patients undergoing elective percutaneous coronary intervention (PCI), periprocedural thrombotic and bleeding complications can lead to increased morbidity and mortality. Whether stronger platelet inhibition by an intensified oral loading strategy (ILS) before PCI impacts on outcomes among these patients in contemporary practice remains unclear. Methods: This multicenter, randomized, assessor-blinded trial teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…The 2017 ESC focused update on dual anti-platelet therapy (DAPT) in CAD recommends clopidogrel (600 mg loading dose, 75 mg daily dose) in addition to aspirin in CCS patients undergoing planned PCI (IA recommendation). 94 This is supported by recent studies in CCS patients undergoing PCI reporting that pre-treatment with the potent platelet P2Y 12 inhibitors ticagrelor (pre-PCI and daily for 30 days) 95 or prasugrel (pre-PCI only), 96 did not reduce periprocedural myocardial injury or MI, with ticagrelor being associated with an increased risk of minor bleeding at 30 days, when compared with clopidogrel. For DAPT-naïve CCS patients who require PCI following diagnostic coronary angiography, it is probably advisable to delay PCI by >2 h or even to the next day, given that a 600 mg loading dose of clopidogrel acts in ∼2 h. However, in those rare instances where ad-hoc PCI is urgently required in DAPT-naïve CCS patients, oral loading with soluble aspirin and ticagrelor or crushed prasugrel may be considered given their faster onset of action (30 min), with clopidogrel given thereafter (600 mg loading dose, 75 mg daily dose).…”
Section: Management Of Periprocedural Myocardial Injury and Type 4a Myocardial Infarctionmentioning
confidence: 89%
“…The 2017 ESC focused update on dual anti-platelet therapy (DAPT) in CAD recommends clopidogrel (600 mg loading dose, 75 mg daily dose) in addition to aspirin in CCS patients undergoing planned PCI (IA recommendation). 94 This is supported by recent studies in CCS patients undergoing PCI reporting that pre-treatment with the potent platelet P2Y 12 inhibitors ticagrelor (pre-PCI and daily for 30 days) 95 or prasugrel (pre-PCI only), 96 did not reduce periprocedural myocardial injury or MI, with ticagrelor being associated with an increased risk of minor bleeding at 30 days, when compared with clopidogrel. For DAPT-naïve CCS patients who require PCI following diagnostic coronary angiography, it is probably advisable to delay PCI by >2 h or even to the next day, given that a 600 mg loading dose of clopidogrel acts in ∼2 h. However, in those rare instances where ad-hoc PCI is urgently required in DAPT-naïve CCS patients, oral loading with soluble aspirin and ticagrelor or crushed prasugrel may be considered given their faster onset of action (30 min), with clopidogrel given thereafter (600 mg loading dose, 75 mg daily dose).…”
Section: Management Of Periprocedural Myocardial Injury and Type 4a Myocardial Infarctionmentioning
confidence: 89%
“…The increased risk of bleeding remains an important concern for patients treated with DAPT after stent implantation (26), especially in east Asian patients who have a higher risk of severe bleeding risk than the western population (27,28). In several previous studies enrolling east Asians, the benefits of stronger P2Y12 inhibitors were partly counterbalanced by an increased risk of bleeding events, which was related to a higher risk of mortality (29)(30)(31). The recommendations for use of ticagrelor over clopidogrel in patients with ACS are based on the clinical trials from western countries and need to be further validated in east Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors proceeded to a pooled analysis of the available randomized trials of using a potent P2Y 12 inhibitors in elective PCI, the aforementioned ALPHEUS trial, and the SASSICAIA (Strategies of Loading With Prasugrel vs. Clopidogrel in PCI-Treated Bio-marker Negative Angina) trial, which concluded that the use of stronger ADP inhibitor was not translated to better ischemic outcomes (OR 1.01, 95% CI, 0.80-1.28, P = 0.94). 54,55 In aggregate, with the available data so far, it seems that clopidogrel remains the standard of care in patients undergoing elective PCI, even in those with a more complex feature. 54,56 Cangrelor, an intravenous reversible antagonist of the platelet P2Y 12 receptor, with a fast onset and offset of action, has been recommended as class IIb across the spectrum of patients with CAD who are naïve of P2Y 12 inhibitor undergoing PCI.…”
Section: Antithrombotic Therapy During Pcimentioning
confidence: 99%